2014
DOI: 10.1007/s00167-014-3427-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of monoblock bicompartmental knee arthroplasty during weight-bearing activities

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Joint kinematics were determined from the 3‐D pose of each implant model using standard conventions for joint rotations and translations [13]. Anteroposterior (AP) condylar translations were evaluated using a previously described contact analysis method [32]. Femoral contact points were evaluated by implementing a nearest‐neighbor algorithm in MATLAB to find the nearest vertex in the tibial insert STL model to each vertex in the femoral STL model by Euclidean distance [32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Joint kinematics were determined from the 3‐D pose of each implant model using standard conventions for joint rotations and translations [13]. Anteroposterior (AP) condylar translations were evaluated using a previously described contact analysis method [32]. Femoral contact points were evaluated by implementing a nearest‐neighbor algorithm in MATLAB to find the nearest vertex in the tibial insert STL model to each vertex in the femoral STL model by Euclidean distance [32].…”
Section: Methodsmentioning
confidence: 99%
“…Anteroposterior (AP) condylar translations were evaluated using a previously described contact analysis method [32]. Femoral contact points were evaluated by implementing a nearest‐neighbor algorithm in MATLAB to find the nearest vertex in the tibial insert STL model to each vertex in the femoral STL model by Euclidean distance [32]. Regions of the insert and femoral component were selected, such that the intercondylar region was excluded during contact analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…distance that are less than the assigned contact cutoff value. As a previous study [22][23][24] reported the average articular cartilage in 5 locations on the femoral trochlea and medial femoral condyles in the equine stifle was estimated to be 2.2 mm, with the thickness of the meniscus taken into account, the contact cutoff for the program was set at 8 mm. Individual data curves and group means were plotted for femorotibial internal/external (IE) rotation, abduction/ adduction and CrCa translations of the medial and lateral femoral condyles as well as the estimated joint contact centroids on the tibial plateau as a function of femorotibial joint extension angle.…”
Section: Kinematic Data Processingmentioning
confidence: 99%